2012
DOI: 10.3390/met2030353
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium-Based Sacrificial Anode Cathodic Protection Coatings (Mg-Rich Primers) for Aluminum Alloys

Abstract: Abstract:Magnesium is electrochemically the most active metal employed in common structural alloys of iron and aluminum. Mg is widely used as a sacrificial anode to provide cathodic protection of underground and undersea metallic structures, ships, submarines, bridges, decks, aircraft and ground transportation systems. Following the same principle of utilizing Mg characteristics in engineering advantages in a decade-long successful R&D effort, Mg powder is now employed in organic coatings (termed as Mg-rich pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 64 publications
(60 reference statements)
0
44
0
Order By: Relevance
“…Magnesium powder is being employed in organic coating (also termed as sacrificial anode) as sacrificial anode pigment to protect aerospace grade aluminum alloy from corrosive environment [3]. Battocchi et al [3,4] investigated electrochemical behavior of Mg rich primer on different aluminum alloys by using electrochemical impedance, open circuit potential and potentiodynamic polarization study. It was found that, Mg rich primers provided excellent sacrificial protection to aluminum substrate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnesium powder is being employed in organic coating (also termed as sacrificial anode) as sacrificial anode pigment to protect aerospace grade aluminum alloy from corrosive environment [3]. Battocchi et al [3,4] investigated electrochemical behavior of Mg rich primer on different aluminum alloys by using electrochemical impedance, open circuit potential and potentiodynamic polarization study. It was found that, Mg rich primers provided excellent sacrificial protection to aluminum substrate.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the presence of carcinogenic Cr (VI) salts, the usage of environment friendly alternative methods have drawn tremendous attention of researchers in last few years worldwide [2]. Magnesium powder is being employed in organic coating (also termed as sacrificial anode) as sacrificial anode pigment to protect aerospace grade aluminum alloy from corrosive environment [3]. Battocchi et al [3,4] investigated electrochemical behavior of Mg rich primer on different aluminum alloys by using electrochemical impedance, open circuit potential and potentiodynamic polarization study.…”
Section: Introductionmentioning
confidence: 99%
“…According to the potentiodynamic polarization and the visual corrosion test results, the efficiency of the coated paints formulations to preserve MS vs corrosion can be graded as follows: F4 > F2 > F5 ~ F7 > F8 > F3 > F8 > F9 ~ F1 > MS. The good corrosion protection is attributed to the alkalinity of the industrial IWP which raises the pH of the iron surface and slows down the CR through the formation of insoluble metal hydroxides . Poly(aniline‐ co ‐anisidine) creates a protective passive layer of iron oxide beneath the paint and works as a physical barrier against the offensive species .…”
Section: Resultsmentioning
confidence: 99%
“…At present, magnesium (Mg), zinc (Zn) and aluminium (Al) are the most commonly used sacrificial metals for CP (Pathak et al, 2012;Parthiban et al, 2008;Yu and Uan 2006) Aluminium has attained considerable merit as the basis for a galvanic anode in oil and gas environments mainly due to its low density, large electrochemical equivalent, availability, thermal and electrical conductivity, high current capacity, low specific weight and reasonable cost (Shibli and Gireesh, 2005;Smoljko et al, 2012;Singleton et al, 2011;Shibli et al, 2007;Liu et al, 2014). However, aluminium suffers from selfpassivation by the formation of a thin, continuous, adherent and passive layer of g -Al 2 O 3 on its surface, which makes it unsuitable to be used as a sacrificial anode.…”
Section: Introductionmentioning
confidence: 99%